Royalties in Mature Upstream Oil and Gas Developments: Progression, Reduction or Abolition - Eduardo G. Pereira (International Review of Law)
Since 2000, over one hundred (100) countries either replaced their existing oil and gas royalty regime or made major amendments to it. However, there is still a continuing debate on whether royalties should be reduced or eliminated, especially in mature oil provinces where fields are declining in production from their plateau rate. Using integrative legal analysis and economic reviews, this work examines the impact of the royalty regime on oil and gas fields with higher emphasis on mature fields and provide recommendations through case studies of countries across multiple continents that depict a progressive fiscal system through royalty implementation, countries that have reduced royalty rates to date, and received favourable fiscal outcomes, and countries that wholly abolished royalty rates altogether. We find that royalty structures in general have advanced from regressive to more progressive rates considering production volumes (daily/cumulative), location (whether onshore, nearshore, shallow-water or deep-water), price, time or category of product (whether crude oil or natural gas). While sliding scale royalties are useful, they nonetheless complicate regimes while failing to address the fundamental drawback of not being linked to costs or underlying project profitability. This makes some marginal projects uneconomic, affecting efforts to maximise economic recovery. It is neither adequate nor economically attractive to fix a royalty amount for fields with production declines in the same manner as those producing at optimal levels. Decreases in royalties for mature fields would incentivize the continuity of their production and, consequently, delay premature field decommissioning, thereby sustaining jobs and domestic energy security.